Kobus Schoeman: A “bridge-builder” practical theologian, bridging divides in the publics of the church, the academy, and society - D.N. Andrew (Acta Theologica)
The concept of “bridge-builder” is used within the context of higher education, understood as a form of engaged scholarship, where researchers function within both the academy and their field of practice or industry. The article focuses on the academic contribution of Prof. Kobus Schoeman whose career can be described as revolving between society, his work as a spiritual leader and minister within the Dutch Reformed Church of South Africa (DRC), and as academic/researcher at the Universities of Pretoria and the Free State. The article focuses first on how his sociology background impacted on his understanding of the church and, more specifically, congregations as a researchable phenomenon, and how insights and experience in statistical analysis accompanied his theological journey and its positive implications for the three publics. Secondly, the article focuses on his theological contribution, illustrated through the themes in his writings, the students he supervised, as well as the projects he led with colleagues locally and globally. Thirdly, the article considers the impact of these two publics ecumenically and societally for the South African context and its global relevance. These endeavours show the many ways in which Schoeman can be described as a “bridge-builder” who refused to be irrelevant and impractical in his theological journey and who demonstrates how the local congregation can become a safe space for reflexive praxis, an “ecclesiology from below” in the truest sense.